A unique brain germinal matrix involvement in cytomegalovirus infected fetuses: A retrospective neurosonographic analysis with outcome correlation. (5th February 2021) - Birnbaum, Roee; Winsteen, Adi; Brusilov, Michael; Wolman, Igal; Ben‐Sira, Liat; Malinger, Gustavo; Krajden Haratz, Karina
Abstract: Objective: To study the clinical significance of brain germinal matrix (GM) changes in cytomegalovirus (CMV) infected fetuses. Method: This is a retrospective analysis. Group A; isolated GM finding, with or without lenticulostriatal vasculopathy (LSV). Group B; non‐isolated lesion. Amniocentesis, urinalysis, postnatal US and developmental assessment, were obtained. Results: Group A and B included 18 and four fetuses, respectively. In group A, mean fetal age at diagnosis was 34.3 weeks (31–38 weeks). In 15/18 (83.3%), the lesion was bilateral and LSV was present in 8/18 (44.4%). Small cysts appeared inside the lesion in 5/18 (27.7%). MRI was normal in 8/18 (44.4%). Subtle or inconclusive findings were reported in the remaining fetuses. Brain ultrasound was normal in 10/18 (55.5%) of newborns. In the remaining, caudothalamic cyst with or without LSV, or isolated LSV were found. All newborns are developing normally at a mean follow‐up age of 33.3 months (+/− 19.6 moths). In group B, all four patients requested for termination of pregnancy. Conclusion: Fetal CMV infection may cause focal GM changes, frequently accompanied by LSV, late in pregnancy. These changes may be isolated, or as part of a more generalized brain damage. When isolated, favorable prognosis is expected. Highlights: What's already known about this topic? Various subtle brain finding are being more frequently diagnosed in cytomegalovirus (CMV) infected fetuses Generally, these findings carry favorable prognosis The germinal matrix may be involved in various fetal brain pathologies What does this study add? Fetal CMV infection may cause specific changes in the germinal matrix (GM) These changes may undergo unique cystic transformation The GM involvement may be isolated (with or without lenticulostriatal vasculopathy) or part of a more general brain insult When isolated the prognosis is good